Markers of endothelial function in migraine patients: Results from a bi-center prospective study. (September 2015) - Fischer, Marlene; Gaul, Charly; Shanib, Hind; Holle, Dagny; Loacker, Lorin; Griesmacher, Andrea; Lackner, Peter; Broessner, Gregor
Background: Numerous studies suggest an increased vascular risk in patients with migraine, in particular in those with aura. A possible link between both conditions might be a dysfunction of the vascular endothelium. This observational study analyzed the endothelial markers angiopoietin-1, angiopoietin-2, Tie-2, sFlt-1 and NT-proBNP for the first time in migraineurs, patients with other primary headache disorders and healthy controls. Methods: Patients with episodic migraine with and without aura, episodic cluster headache, tension-type headache and healthy controls were included. Blood samples were obtained during migraine attacks and headache-free periods in migraineurs, in and out of bout in cluster headache and during headache-free periods in tension-type headache and healthy individuals to analyze markers of endothelial function. Results: No significant difference in endothelial markers between migraine, other headache disorders and healthy controls was detected. There was no significant difference between migraine attacks and headache-free intervals. Additionally, no distinction could be found between migraine with and without aura. Discussion: The endothelial markers analyzed do not display a characteristic pattern in different headache disorders especially migraine compared to healthy controls. The novel findings of our study indicate that factors other than endothelial dysfunction seem to be responsible for the at least statistical association of migraine with vascular disease.